(untitled) (KULT_online, 2024)
Refugee camps, even if they were established 75 years ago, are still considered temporary settlements. What if these camps were planned as permanent cities, designed to meet the needs of displaced populations? War Victims and the Right to a City: From Damascus to Zaatari by Hind Al-Shoubaki is an attempt to approach this question by applying the concepts of “temporary cities,” “urbiside,” and “urban emergency integrated planning” to a cross-case synthesis. The book uses interviews and historical analysis in Syria and Jordan to reflect on the camp-city relationship in a variety of spheres.